A Randomized Controlled Phase 2 Dose-Finding Trial to Evaluate the Efficacy and Safety of Camostat in the Treatment of Painful Chronic Pancreatitis: The TACTIC Study - Hart, Phil. A.; Osypchuk, Yu.; Hovbakh, I.; Shah, R. J.; Nieto, J.; Cote, G. A.; Avgaitis, S.; Kremzer, O.; Buxbaum, J.; Inamdar, S.; Fass, R.; Phillips, R. W.; et al. (My University, 2024)
BACKGROUND & AIMS: Chronic pancreatitis (CP) causes an abdominal pain syndrome associated with poor quality of life. We conducted a clinical trial to further investigate the efficacy and safety of camostat, an oral serine protease inhibitor that has been used to alleviate pain in CP. METHODS: This was a double-blind randomized controlled trial that enrolled adults with CP with a baseline average daily worst pain score 4 on a numeric rating system. Participants were randomized (1:1:1:1) to receive camostat at 100, 200, or 300 mg 3 times daily or placebo. The primary end point was a 4-week change from baseline in the mean daily worst pain intensity score (0–10 on a numeric rating system) using a mixed model repeated measure analysis. Secondary end points included changes in alternate pain end points, quality of life, and safety. RESULTS: A total of 264 participants with CP were randomized. Changes in pain from baseline were similar between the camostat groups and placebo, with differences of least squares means of –0.11 (95% CI, –0.90 to 0.68), –0.04 (95% CI, –0.85 to 0.78), and –0.11 (95% CI, –0.94 to 0.73) for the 100 mg, 200 mg, and 300 mg groups, respectively. Multiple subgroup analyses were similar for the primary end point, and no differences were observed in any of the secondary end points. Treatment-emergent adverse events attributed to the study drug were identified in 42 participants (16.0%). CONCLUSION: We were not able to reject the null hypothesis of no difference in improvements in pain or quality of life outcomes in participants with painful CP who received camostat compared with placebo. Studies are needed to further define mechanisms of pain in CP to guide future clinical trials, including minimizing placebo responses and selecting targeted therapies.
Keywords: Serine Protease Inhibitor; Analgesia; Morbidity; Quality of Life